PELAKSANAAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI SMA - Yoti S F Faot; Simon Sabon Ola; Ari Data (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The degradation of national character due to the flow of technology demands an educational solution through the Pancasila Student Profile Strengthening Project (P5) to build students' moral values. This study aims to evaluate the implementation of P5 in character building at SMAN 6 Kupang, with a focus on module development and the implementation of character dimensions. Using a qualitative evaluation paradigm, data were collected through interviews, observations, and documentation, then analyzed using the Marshall and Rossman model. The research steps included five planning stages: theme selection, time allocation, goal setting, module development, and assessment. The findings indicate that module development followed standard procedures, with an emphasis on the theme of Local Wisdom. Character implementation was analyzed through Albert Bandura's four stages of social learning theory: attention, retention, reproduction, and motivation. The results confirmed that ten intensive meetings on one theme were able to increase students' active participation and understanding of gratitude, environmental conservation, and cultural diversity. Although not optimal, this project had a positive impact on students' interpersonal development. The main conclusion confirms that the effectiveness of P5 is highly dependent on the systematic planning and students' ability to embody the six profile dimensions in their daily lives. The integration of Bandura's theory has been proven to help internalize characters that are in line with the school's vision and national ideology in a sustainable manner to create a superior, competent, innovative, religious, responsible, disciplined, honest, and tolerant generation. ABSTRAK Degradasi karakter bangsa akibat arus teknologi menuntut solusi edukatif melalui Projek Penguatan Profil Pelajar Pancasila (P5) guna membangun nilai moral peserta didik. Penelitian ini bertujuan mengevaluasi pelaksanaan P5 dalam pembentukan karakter di SMAN 6 Kupang, dengan fokus pada penyusunan modul serta implementasi dimensi karakter. Menggunakan paradigma kualitatif jenis evaluasi, data dikumpulkan melalui wawancara, observasi, dan dokumentasi, lalu dianalisis dengan model Marshall dan Rossman. Langkah penelitian mencakup lima tahapan perencanaan: pemilihan tema, alokasi waktu, penentuan tujuan, pembuatan modul, dan asesmen. Temuan menunjukkan bahwa penyusunan modul telah mengikuti prosedur standar, dengan penekanan pada tema Kearifan Lokal. Implementasi karakter dianalisis melalui empat tahapan teori belajar sosial Albert Bandura, yakni perhatian, retensi, reproduksi, dan motivasi. Hasil penelitian mengonfirmasi bahwa sepuluh pertemuan intensif pada satu tema mampu meningkatkan partisipasi aktif serta pemahaman siswa mengenai rasa syukur, pelestarian alam, dan keragaman budaya. Meskipun belum optimal, projek ini memberikan dampak positif terhadap perkembangan interpersonal peserta didik. Simpulan utama menegaskan bahwa efektivitas P5 sangat bergantung pada sistematika perencanaan dan kemampuan siswa mengejawantahkan enam dimensi profil dalam keseharian. Integrasi teori Bandura terbukti membantu internalisasi karakter yang selaras dengan visi sekolah dan ideologi nasional secara berkelanjutan demi mewujudkan generasi yang unggul, kompeten, inovatif, religius, bertanggung jawab, disiplin, jujur, serta toleran.